Perceptions of leadership behavior and the relationship to athletes among Scandinavian coaches - Enoksen, E.; Fahlström, P. G.; Johansen, B. T.; Hageskog, C.-A.; Behrend Christensen, J.; Høigaard, R. (Scandinavian Sport Studies Forum, 2014)
The purpose of this study was to investigate the relationship between the perceptions of leadership behavior and coach-athlete relationship in Scandinavian coaches. A secondary purpose was to investigate if differences in national sport education, level of coaching and coaching experiences in individual or team sport have an influence on leadership behavior and coach-athlete relationships. One hundred and forty nine coaches at international level or national top level from Denmark, Norway and Sweden participated in this study (134 male and 15 female). The methods of investigation were Chelladurai`s Leadership scale of sport (LSS) (Chelladurai & Saleh, 1980) and Jowett`s coach-athlete relationship perspective (Jowett & Wyllemann, 2006). The results showed that the most frequent self-reported behavioral components between the described coach-athlete relationship subscales and preferred leadership behavior among Scandinavian top-level coaches were training and instructions, positive feedback and democratic behavior, respectively. The study also revealed a positive coach-athlete relationship between (1) commitment and training and instruction, (2) positive feedback and social support, and (3) between complementarities and training and instruction behavior. A significant difference was found between top coaches in Denmark and Sweden on commitment and complementarity, and more experienced coaches used significantly more training and instruction and social support in their coaching than did less experienced coaches. Coaches in team sports reported more autocratic behavior and less democratic behavior than coaches in individual sports.